2016
DOI: 10.1055/s-0042-101023
|View full text |Cite
|
Sign up to set email alerts
|

Mapping international practice patterns in EUS-guided tissue sampling: outcome of a global survey

Abstract: Background and study aims: Although Endoscopic Ultrasound (EUS)-guided tissue sampling is widely used, the optimal sampling strategy remains subject of debate. We evaluated practice patterns within the international endosonographic community. Patients and methods: An online questionnaire was sent to 400 endosonographers from the United States, Europe, and Asia. Results: A total of 186 (47 %) endosonographers participated: United States 54 (29 %), Europe 85 (46 %), and Asia 47 (25 %). European (75 %) and Asian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 37 publications
2
61
0
Order By: Relevance
“…In our survey, the cell block technique is applied in all echoendoscopy units which performed EUS-FNA. These data are in line with the results of van Riet et al [6] which demonstrated that the majority of respondents applied the cell block technique (85%), but it was used to a lesser extent in Europe (85%) and Asia (70%) than in the United States (96%). DOI: 10.1159/000495524 Also noteworthy is the general involvement of at least 1 ultrasonographer in multidisciplinary meetings (61.9%) and the existence of a local EUS database (57.1%).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our survey, the cell block technique is applied in all echoendoscopy units which performed EUS-FNA. These data are in line with the results of van Riet et al [6] which demonstrated that the majority of respondents applied the cell block technique (85%), but it was used to a lesser extent in Europe (85%) and Asia (70%) than in the United States (96%). DOI: 10.1159/000495524 Also noteworthy is the general involvement of at least 1 ultrasonographer in multidisciplinary meetings (61.9%) and the existence of a local EUS database (57.1%).…”
Section: Discussionsupporting
confidence: 91%
“…van Riet PA et al showed only half of the European and Asian respondents used ROSE. In this study, respondents who refrain from using ROSE consider limited pathology staff (74%) and disbelieve in its additive value (32%) as the main reasons for omitting it [6]. These data were corroborated by DiMaio et al [8] in a survey study which demonstrated that the vast majority of American ultrasonographers (76.2%) utilize ROSE when performing EUS-FNA.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…This has led to the establishment of ROSE as the default practice in many institutions where EUS-FNA or EBUS-FNA is offered. A survey of endosonologists indicated that ROSE was used more often by US (98%) than by European (48%) or Asian (55%) respondents [10].…”
mentioning
confidence: 99%